PPP Despite Real Shocks: An Empirical Analysis of the Norwegian Real Exchange Rate - Q. Farooq Akram (Norges Bank, 2000)
Despite the emerging consensus on the validity of purchasing power parity (PPP) between trading countries in the long run, empirical evidence in favour of the PPP theory is scarce in data predominantly exposed to real shocks. This paper tests for PPP between Norway and its trading partners using quarterly observations from the post Bretton Woods period, in which the Norwegian economy has been exposed to numerous real shocks such as frequent revaluations of oil and gas resources through new discoveries and price fluctuations. The paper undertakes an extensive examination of the behaviour of the Norwegian real and nominal exchange rates and shows that it is remarkably consistent with the PPP theory. Moreover, convergence towards the equilibrium level appears relatively fast; our estimate of the half life of a deviation from the equilibrium level is just six quarters. This is partly attributed to the Norwegian government's policies aimed at preserving the competitiveness of the economy and the system of centralized wage bargaining.
hdl:11250/2500404
Keywords: C22; C32; C51; E31; E31; E58; F41; J51; 330; PPP; purchasing power parity; Dutch disease; real exchange rate; oil prices; centralised wage bargaining; exchange rate policy; cointegration analysis